Numerical Investigation of the Behavior of Reinforced Concrete Beam Reinforced with FRP Bars - Mohammed, Rania Salih; Fangyuan, Zhou (Civil Engineering Journal, 2019)
In this study, the behavior of reinforced concrete beams reinforced with FRP bars was investigated. A total of seventeen models were carried out based on the finite element software (ABAQUS). The concrete damage plasticity modeling was considered. Two types of fiber polymer bars, CFRP and GFRP as longitudinal reinforcement for concrete beam were used. The validation of numerical results was confirmed by experimental results, then the parametric study was conducted to evaluate the effect of change in different parameters, such as (diameter size, number of bars), type of FRP bars, longitudinal arrangement for FRP bars. All results were analyzed and discussed through, load-deflection diagram, according, to the difference parameter considered. The results showed that the use of FRP bars in rebar concrete beam improves the beam stiffness and enhance the cracking load. The load capacity enhanced in the range of (7.88-64.82%) when used CFRP bars. The load-carrying capacity of beams strengthened with CFRP is higher than that of strengthened with GFRP. Furthermore, the use of FRP bars in bottom and steel in top reinforcement is useful to overcome the large deflection, and improving the beam ductility. Finally, the results of finite element models were compared with the prediction equation, according to ACI440.1R-15.